EFEKTIVITAS MEDIA GADGET MENURUT TEORI USES AND GRATIFICATION DALAM PEMBELAJARAN EKONOMI GUNA MEMBANGUN KETERAMPILAN SOSIAL SISWA KELAS XI DI SMA NEGERI 1 SIGI - Kapile, Natalia Veronica; Hasan, Hasan; Nuraedah, Nuraedah (Katalogis, 2020)
The main problem in this study is that most students own and use gadgets as a learning medium of economic. It is information from the students who reveal that economic teachers demand the students to use the device, some students who are new to using gadgets on particular material in economics subject. The use of gadgets as a medium of learning in the classroom needs to be balanced with the social skills of students. It needs to be a concern that the use of gadgets does not make students an individualistic and "autistic" figures. Besides, there should be prevention that they will not have engrossed themselves with gadgets, which makes them ignore their surroundings, including friends. The purpose of this research is to describe The Effectiveness of Gadgets based on the Uses and Gratification Theory in Economic Learning to Build the Social Skills of Grade XI Students at SMA Negeri 1 Sigi. This research used descriptive and qualitative methods. The results indicated that under the theory of needs and motives for the use of media or Uses and Gratification, at least some aspects can be used with teachers being able to build social skills in class XI students of SMA Negeri 1 Sigi, namely: 1) Cognitive Skills, 2) Affective Skills, 3) Personal Integrative Needs; 4) Social Integrative Needs, 5) Escapist Needs. Teachers can carry out the use of gadget media in economic learning effectively, can develop economic learning materials that fit the needs of new knowledge for students. Teachers can make positive affective efforts (actions), and students can learn themselves or be actively involved (participative) in knowing new economic learning materials, then simultaneously in building social skills Grade XI Students at SMA Negeri 1 Sigi through the use of gadget.